TPM: Factors And Barrier Analysis Towards Maintenance efficiency in Manufacturing Industry - Ahmad, Ahmad Nur Aizat; Ahmad, Md Fauzi; Hamid, Norhadilah Abdul; Hamid, Nor Aziati Abdul; Ruslan, Rumaizah; Lamani, Edwin; Nawanir, Gusman; Bakri, Adnan; Rahim, Mustaqqim Abdul (International Journal of Supply Chain Management, 2020)
Previous studies indicated that the autonomous maintenance barrier factors are affected the maintenance efficiency. However, most of these studies were conducted in the service industry but not in the manufacturing industry. Therefore, the purpose of this research is to identify the most critical barrier factors towards maintenance efficiency and also to identify the relationship between autonomous maintenance barrier factors and maintenance efficiency in manufacturing industries. Five research hypotheses were examined while considering the autonomous maintenance barrier factors which including lack of top management commitment, lack of training, lack of maintenance knowledge, resistance by employees, and lack of tools and instrument. The findings of this study revealed that lack of tools and instrument is the most critical barrier factor. This quantitative case study is crucial to the manufacturing industry in Malaysia because it provides a broad insight into the correlation between the autonomous maintenance barrier factor and maintenance efficiency.